Productivity Estimation of any Manufacturing Industry Using Fuzzy Logic in MATLAB Software - Shubham Vishwakarma; Akash Tomar (International Journal of Manufacturing and Production Engineering, 2024)
In every industry/organization Labor Productivity plays a major part in the overall growth and production. Many time it is observed that industries do not attain their desired goals due to poor labor productivity. Labor Productivity is dependent on many different factors like Delay in Payment, management supervision over workers, proper work planning and scheduling, poor site safety program, lack of financial motivation system, etc. In this study, we estimated labor productivity in various industries by gathering extensive data, conducting surveys, and interviewing industry professionals. The primary objective of this project is to determine the factors that affect labor productivity. in any industry. The 50 factors of estimating Labor Productivity are chosen from the industrial projects. The survey was done through wide data collection, questionnaire survey and experts views which are then ranked through RII scale. The ranking is done through RII and then it is used for deciding top ranking factors which are responsible for Labor Productivity. After deciding factors for estimating Labor Productivity, fuzzy logic and ANN are used in MATLAB environment.
Keywords: FUZZY LOGIC; Industrial engineering; Performance Metrics; Workforce efficiency; advanced control systems; computational analysis; data evaluation; fuzzy inference systems; labour productivity; matlab software; membership functions; productivity analysis; rule-based systems